Petroleum source rock evaluation of the Sebahat and Ganduman Formations, Dent Peninsula, Eastern Sabah, Malaysia - Mustapha, K.A.; Abdullah, W.H. (Elsevier, 2013)
The Sebahat (Middle Miocene to Early Pliocene) and Ganduman (Early Pliocene to Late Pliocene) Formations comprise part of the Dent Group. The onshore Sebahat and Ganduman Formations form part of the sedimentary sequence within the Sandakan sub-basin which continues offshore in the southern portion of the Sulu Sea off Eastern Sabah. The Ganduman Formation lies conformably on the Sebahat Formation. The shaly Sebahat Formation represents a distal holomarine facies while the sandy Ganduman Formation represents the proximal unit of a fluvial–deltaic system.